Reflexive Dialogues: Interaction and Writing as External Components of Personal Reflexivity - Caetano, Ana (Sociological research online, 2017)
Margaret Archer’s work suggests that reflexivity is exercised through internal dialogues, in which subjects talk to themselves in order to clarify ideas, mull over problems, make plans, and take decisions. The present article argues that the exercise of reflexive competences is not limited to the privacy of individual minds, but that there is also an external component, which can lend the concept a broader analytical scope. Using the results of qualitative research focused on the social mechanisms of personal reflexivity, including biographical interviews, the article examines two other modalities of exercising reflexivity: external conversations in interaction contexts and writing practices (autobiographical, creative, communicational, and organisational). It also looks at the differential activation of reflexivity according to both the subjects’ different positions in social space and inter- and intra-contextual variations.